Azerbaijan's Policy of Destruction and Appropriation of Artsakh Cultural Heritage as a Disruption of the Peace Agenda - Tigranyan, Armine (ՀՊՏՀ «Տնտեսագետ» հրատ․)
As a result of the war initiated by Azerbaijan in 2020 and the subsequent actions that followed, including the transition of Artsakh’s territories to Azerbaijani control, the nine-month blockade of the Lachin Corridor prior to the forced displacement of over 120,000 Armenians on September 19, 2023, Azerbaijan has systematically destroyed and continues to destroy the rich and unique cultural heritage of Artsakh. This coordinated policy strikes a blow to the planet's cultural diversity, undermines the concept of tolerance as enshrined in international law, and fosters hatred and racial discrimination in the region. These actions ultimately neutralize eﬀorts to establish a peace agenda, deepening divisions and escalating tensions. The article presents Azerbaijan's policy of destruction and appropriation of Artsakh's cultural heritage from 2020 to 2024. It documents the instances of heritage destruction, categorizing them by type, and discusses the impact of this policy on the continuation of the conﬂict, the fostering of intolerance, and the disruption of the peace agenda. International organizations have emphasized that the destruction of cultural heritage is an ongoing war. Azerbaijan is obligated under international law to respect all cultural values, as stated in UNESCO's principles, which recognize the contribution of every nation's heritage to global diversity. Azerbaijan's actions violate these obligations, further hindering peace and reconciliation eﬀorts in the region. Ադրբեջանի այս գործողությունները խաթարում են նաև խաղաղության օրակարգի հաստատման ջանքերը և սրում լարվածությունը։ Հոդվածում ներկայացվում է 2020-2024 թվականների ընթացքում Ադրբեջանի կողմից Արցախի մշակութային ժառանգության ոչնչացման և յուրացման քաղաքականությունը։ Փաստագրելով ժառանգության ոչնչացման դեպքերը՝ դրանք դասակարգվում են ըստ ուղղությունների, և քննարկում է այս քաղաքականության ազդեցությունը հակամարտության շարունակման, անհանդուրժողականության խթանման և խաղաղության օրակարգի խաթարման վրա։ Միջազգային կազմակերպություններն ընդգծում են, որ մշակութային ժառանգության ոչնչացումը շարունակական պատերազմ է։ Ադրբեջանը, միջազգային իրավունքի համաձայն, պարտավոր է հարգել ամեն մի մշակութային արժեք, ինչպես սահմ անված է ՅՈՒՆԵՍԿՕ-ի սկզբունքներում, որոնք ճանաչում են յուրաքանչյուր ազգի ժառանգության ներդրումը համաշխարհային մշակութային բազմազանության մեջ։ Ադրբեջանի գործ ողությունները խախտում են այս պարտավորությունները՝ էլ ավելի խոչընդոտելով խաղաղության ջանքերը տարածաշրջանում։ В результате войны, начатой Азербайджаном в 2020 году, и последующих действий, включая переход территорий Арцаха под контроль Азербайджана, девятимесячной блокады Лачинского коридора и вынужденного переселения более 120 000 армян 19 сентября 2023 года, Азербайджан систематически уничтожает богатое и уникальное культурное наследие Арцаха. Эта скоординированная политика наносит удар по культурному разнообразию планеты, подрывает концепцию толерантности, закрепленную в международном праве, и способствует распространению ненависти и расовой дискриминации в регионе. Эти действия в конечном итоге нейтрализуют усилия по установлению мирной повестки, углубляют разделение и усиливают напря женность. В статье представлена политика Азербайджана по уничтожению и присвоению культурного наследия Арцаха с 2020 по 2024 год. В ней документируются случаи уничтожения наследия, классифицируются по типу и обсуждается влияние этой политики на продолжение конфликта, содействие нетерпимости и нарушение мирной повестки. Международные организации под черкивают, что уничтожение культурного наследия — это продолжающаяся война. Азербайджан обязан по международному праву уважать все культурные ценности, как указано в прин ципах ЮНЕСКО, которые признают вклад наследия каждой нации в мировое разнообразие. Действия Азербайджана нарушают эти обязательства, что еще больше препятствует усилиям по установлению мира и примирению в регионе.
Keywords: Security and challenges